HOW DOES A UNIVERSITY OF CHOICE COME TO STUDENTS’ MIND? FROM THE ASPECT OF THE E-SERVICESCAPE OF UNIVERSITY’S WEBSITE - Kardina Yudha Parwati (Manajemen Bisnis, 2020)
The goals of this study are want to explore the effect of the e-servicescape on private university’s website towards student’s intention to use the service. This study also wants to know about how does the effect of the e-servicescape towards perceived private university’s service quality, and how does the perceived private university’s service quality effect towards student’s intention to use that service. This study is explanatory research which is using a quantitative approach. A survey using a questionnaire was conducted to collect the data. Moreover, the data of this study was measure in 5 rates Likert’s scale and then analyzed using Partial Least Square Method with SmartPLS3 software. The population of this study are the students of a private university in Indonesia. The sample of this study is 165 students of a private university in Indonesia. Purposive sampling technique is used by criteria as follow, the respondent must be private university students and have been seen and looking about their university’s website when still school leavers back then. The result of this study is that there is a significant influence of the e-servicescape to the perceived service quality. Furthermore, perceived service quality also found to have a significant influence on the student’s intention to use the private university service. This study also found that e-servicescape only is not enough to influence the student’s intention to use the private university service, and must be mediated by perceived service quality.